Incidence and influencing factors of fertility concerns in breast cancer in young women: a systematic review and meta-analysis - Chen, Lijuan; Shen, Jiali; Jiang, Hongzhan; Lin, Huihui; He, Jiaxi; Fan, Siyue; Yang, Liping; Yu, Doudou; Qiu, Rongliang; Lin, Ende (Frontiers in Oncology, 2023)
Objective: This systematic review and meta-analysis aimed to evaluate the prevalence and influencing factors of fertility concerns in breast cancer in young women. Methods: A literature search on PubMed, Embase, Web of Science, and Cochrane Library databases was conducted up to February 2023 and was analyzed (Revman 5.4 software) in this study. The papers were chosen based on inclusion standards, and two researchers independently extracted the data. The included studies' quality was evaluated using criteria set out by the Agency for Healthcare Research and Quality. To identify significant variations among the risk factors, odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) were utilized. Results: A total of 7 studies that included 1579 breast cancer in young women were enrolled in the study. The results showed that for breast cancer in young women, the incidence of fertility concerns 53％(95％CI [0.45,0.58]). The results showed that education (2.65, 95% CI 1.65-5.63), full-time work (0.12, 95% CI 1.03-1.93), fertility intentions (7.84, 95% CI 1.50-37.4), depression level (1.25, 95% CI 1.03-1.5), and endocrine therapy (1.32, 95% CI 1.08-1.62) were risk factors for fertility concerns in young women with BC. Having a partner (0.41, 95% CI 0.33-0.5), ≥1 child (0.3, 95% CI 0.22-0.4) were identified as protective factors against fertility concerns in young women with BC .Conclusions: The incidence of fertility concerns in breast cancer in young women is at a moderately high level. we should pay more attention to the risk factors of fertility concerns to help breast cancer in young women cope with their fertility concerns and promote their psychological well-being.